Elevating Science to Detect Unsolvable Problems - Williams, Andy (My University, 2022)
This article explores the systematic causes for problems in science to be effectively unsolvable. These causes are classed as problems of cognition, and problems of awareness, since, problems can’t be defined or solved through conscious effort unless there is an awareness of the need for a problem to be defined, and/or awareness of the need for a solution. For this reason problems might be unsolvable not only because they are too complex to be solved through type 1 or type 2 cognitive reasoning, but also because of lack of awareness they exist. This article explores both systemic sources of lack of awareness and new techniques which might address that lack, as well as exploring the emerging science of General Collective Intelligence which promises to significantly increase capacity to address lack of collective cognitive ability.
Keywords: General Collective Intelligence; science policy; wicked problems